Lower limb joint kinetics and ankle joint stiffness in the sprint start push-off - Charalambous, L.; Irwin, G.; Bezodis, I. N.; Kerwin, D. (Journal of Sports Sciences, 2011)
Sprint push-off technique is fundamental to sprint performance and joint stiffness has been identified as a performance-related variable during dynamic movements. However, joint stiffness for the push-off and its relationship with performance (times and velocities) has not been reported. The aim of this study was to quantify and explain lower limb net joint moments and mechanical powers, and ankle stiffness during the first stance phase of the push-off. One elite sprinter performed 10 maximal sprint starts. An automatic motion analysis system (CODA, 200 Hz) with synchronized force plates (Kistler, 1000 Hz) collected kinematic profiles at the hip, knee, and ankle and ground reaction forces, providing input for inverse dynamics analyses. The lower-limb joints predominately extended and revealed a proximal-to-distal sequential pattern of maximal extensor angular velocity and positive power production. Pearson correlations revealed relationships (P < 0.05) between ankle stiffness (5.93± 0.75 N · m · deg-1) and selected performance variables. Relationships between negative power phase ankle stiffness and horizontal (r = -0.79) and vertical (r = 0.74) centre of mass velocities were opposite in direction to the positive power phase ankle stiffness (horizontal: r = 0.85; vertical: r = -0.54). Thus ankle stiffness may affect the goals of the sprint push-off in different ways, depending on the phase of stance considered.